2023
DOI: 10.1186/s12886-023-02941-1
|View full text |Cite
|
Sign up to set email alerts
|

Implanting toric implantable collamer lens displays better astigmatism correction than implantable collamer lens combined with manually limbal relaxing incision

Abstract: Background This retrospective study aimed to compare the outcomes of toric implantable collamer lens (TICL) surgery with those of implantable collamer lens (ICL) implantation combined with limbal relaxing incision (LRI) in patients with low myopia and astigmatism. Methods A total of 40 eyes of 28 patients who underwent TICL implantation and 40 eyes of 27 patients who underwent ICL implantation combined with manually LRI between 2021 and 2022 were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
2
1
Order By: Relevance
“…In this study, both groups of patients achieved signi cant and stable improvement in UCVA and BCVA postoperatively, similar to previous research results [30,[33][34][35][36]. Meanwhile, the CDVA and UDVA of the LRI group were better than those of the TICL group at 1 month and 3 months postoperatively, which may be related to the accurate correction of AST.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, both groups of patients achieved signi cant and stable improvement in UCVA and BCVA postoperatively, similar to previous research results [30,[33][34][35][36]. Meanwhile, the CDVA and UDVA of the LRI group were better than those of the TICL group at 1 month and 3 months postoperatively, which may be related to the accurate correction of AST.…”
Section: Discussionsupporting
confidence: 89%
“…Yang's retrospective study found that SIA in the LRI group was reduced signi cantly during the 3 months after surgery, indicating a trend of loss of the astigmatic correction effect and undercorrection over time. However, Yang et al also found that SIA in the TICL group was not signi cantly reduced and was slightly higher than that in the LRI group at 3 months postoperatively [30]. In our study, the SIA of the TICL group was lower than that of the LRI group at 3 months postoperatively, and there was no signi cant difference between the two groups.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…For cataract cases, we discuss the use of Toric IOLs to correct low degrees of corneal astigmatism, however it is not the only resolution. Low-degree corneal astigmatism could be, otherwise, corrected by laser vision correction or limbal relaxing incisions [25][26][27][28] . further research is needed to evaluate the accuracy of each resolution.…”
Section: Discussionmentioning
confidence: 99%